Imaging Neurovascular Function and Functional Recovery after Stroke in the Rat Striatum Using Forepaw Stimulation. Issue 9 (September 2014) - Shih, Yen-Yu Ian; Huang, Shiliang; Chen, You-Yin; Lai, Hsin-Yi; Kao, Yu-Chieh Jill; Du, Fang; Hui, Edward S; Duong, Timothy Q
Negative functional magnetic resonance imaging (fMRI) response in the striatum has been observed in several studies during peripheral sensory stimulation, but its relationship between local field potential (LFP) remains to be elucidated. We performed cerebral blood volume (CBV) fMRI and LFP recordings in normal rats during graded noxious forepaw stimulation at nine stimulus pulse widths. Albeit high LFP-CBV correlation was found in the ipsilateral and contralateral sensory cortices (r = 0.89 and 0.95, respectively), the striatal CBV responses were neither positively, nor negatively correlated with LFP (r = 0.04), demonstrating that the negative striatal CBV response is not originated from net regional inhibition. To further identify whether this negative CBV response can serve as a marker for striatal functional recovery, two groups of rats ( n = 5 each) underwent 20- and 45-minute middle cerebral artery occlusion (MCAO) were studied. No CBV response was found in the ipsilateral striatum in both groups immediately after stroke. Improved striatal CBV response was observed on day 28 in the 20-minute MCAO group compared with the 45-minute MCAO group ( P <0.05). This study shows that fMRI signals could differ significantly from LFP and that the observed negative CBV response has potential to serve as a marker for striatal functional integrity in rats.